The Effects of Self-Esteem and Peer Social Support on the Academic Resilience of Students Actively Involved in Organizations - Ersa Lanang Sanjaya; Raissa Nabila Chusaini (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Students who are actively involved in campus organizations face challenges in balancing academic demands with organizational responsibilities. This study aimed to examine the influence of self-esteem and peer social support on the academic resilience of these students. The instruments used were the Rosenberg Self-Esteem Scale, Peer Social Support from Friends scale, and the Academic Resilience Scale. A purposive sampling technique was used, involving 200 students actively engaged in organizational activities. The results of the analysis showed that self-esteem and peer social support had a significant effect on academic resilience. The findings suggested that students with higher levels of self-esteem and stronger peer support tend to withstand academic pressure more effectively and fulfil their organizational responsibilities. Thus, fostering self-esteem and creating a supportive peer environment could serve as key strategies to enhance academic resilience among organizationally active students.